PERUBAHAN TINGGI GELOMBANG LAUT AKIBAT ADANYA STRUKTUR TENGGELAM - REZA TRIAFSA GAUS, MOCHAMAD
Breakwater is a structure which main function is to protect the coast from ocean waves by reducing its energy. This study is focused on testing four submerged breakwater designs wherein this type of breakwater is placed on the seabed and the height does not exceed still water level. The testing was conducted through physical laboratory testing using four breakwater scenarios, each of which differs in the height of the breakwater itself (the amount of breakwater stack) and to measure the wave elevation, four wave probes were used. Three wave probes were placed in front of the breakwater and one wave probe was placed behind the breakwater. Reduction of wave energy is marked by wave height reduction after passing through the breakwater. Changes in wave heights will then be compared with four breakwater scenarios for the correlation to be seen. Results showed that the first breakwater scenario which is the highest breakwater can dampen the waves up to 56% while the rest of breakwater scenarios gave similar level of dampening, at around 40%.